Efetividade do Protocolo Sepse implantado em um hospital no município de Fortaleza, Ceará, Brasil - Melo, Thaissa Pinto de (2018)
Introduction: Despite many advances in the understanding of sepsis and recent research indicating better results in its treatment, this entity still has an epidemic incidence and an unacceptably high mortality rate. Several studies have shown that the implantation of care protocols significantly decreases mortality. Objective: to evaluate the effectiveness of the protocol in a public hospital in the city of Fortaleza, Ceará, Brazil, and to recognize the limitations of this instrument. Methodology: longituadinal with quanti-quali approach, with retrospective and prospective phases. Results: The three-hour package was considered in the series, but there was no reduction in overall mortality when compared to the non-protocol period (p = 0.22). The predictive parameters of hospital mortality were: diagnosis of septic shock (p = 0.01), altered creatinine (p = 0.02), altered body temperature (p = 0.05), advanced age, number of SIRS criteria (p = 0.02) and protocol opening period (p = 0.01). Regarding the qualitative perspective, the professionals recognize the importance of the sepsis protocol to reduce sepsis mortality in the hospital. However, there are limitations on the implementation process of the recommendations. These difficulties arise from noises of communication that interfere with the offer of full care. Conclusion: the use of the protocol is not associated with the reduction of sepsis mortality, but operational aspects should be reviewed, such as the implementation of recommendations. These difficulties arise from noises of communication that interfere with the offer of full care.